Maternal factors and child health conditions at birth associated with preterm deaths in a tertiary health facility in Ghana: A retrospective analysis - Seth Kwaku Afagbedzi; Yakubu Alhassan; Deda Ogum Alangea; Henrietta Taylor (Frontiers Media S.A., 2023)
BackgroundPreterm birth continues to be a leading cause of death for children under the age of 5 globally. This issue carries significant economic, psychological, and social costs for the families affected. Therefore, it is important to utilize available data to further research and understand the risk factors for preterm death.ObjectiveThe objective of this study was to determine maternal and infant complications that influence preterm deaths in a tertiary health facility in Ghana.MethodsA retrospective analysis of data on preterm newborns was conducted at the neonatal intensive care unit of Korle Bu Teaching Hospital (KBTH NICU) in Ghana, covering the period January 2017 to May 2019. Pearson's Chi-square test of association was used to identify factors that were significantly associated with preterm death after admission at the NICU. The Poisson regression model was used to determine the risk factors of preterm death before discharge after admission to the NICU.ResultsOf the 1,203 preterm newborns admitted to the NICU in about two and half years, 355 (29.5%) died before discharge, 7.0% (n = 84) had normal birth weight (>2.5 kg), 3.3% (n = 40) had congenital anomalies and 30.5% (n = 367) were born between 34 and 37 gestational week. All 29 preterm newborns between the 18-25 gestational week died. None of the maternal conditions were significant risk factors of preterm death in the multivariable analysis. The risk of death at discharge was higher among preterm newborns with complications including hemorrhagic/hematological disorders of fetus (aRRR: 4.20, 95% CI: [1.70-10.35], p = 0.002), fetus/newborn infections (aRRR: 3.04, 95% CI: [1.02-9.04], p = 0.046), respiratory disorders (aRRR: 13.08, 95% CI: [5.50-31.10], p < 0.001), fetal growth disorders/restrictons (aRRR: 8.62, 95% CI: [3.64-20.43], p < 0.001) and other complications (aRRR: 14.57, 95% CI: [5.93-35.77], p < 0.001).ConclusionThis study demonstrate that maternal factors are not significant risk factors of preterm deaths. Gestational age, birth weight, presence of complications and congenital anomalies at birth are significantly associated with preterm deaths. Interventions should focus more on child health conditions at birth to reduce the death of preterm newborns.